PENGARUH PEMBERIAN REWARDTERHADAPMOTIVASI BELAJARSISWA:STUDIDI KELAS TINGGI SD INPRES 3/77 PANYILI KECAMATAN PALAKKA KABUPATEN BONE - Abd Kadir. A; Sudarto Sudarto; Dandi Dandi (Bajang Institute, 2022)
This study was a cause-and-effect correlation study that aimed to determine whether there was or there was not an effect of rewarding to the learning motivation of students in the high grades of SD Inpres 3/77 Panyili. The research data was obtained through a questionnaire. The population in the study was all of the high-grade students of SD Inpres 3/77 Panyili for the 2021/2022 academic year, in acount 48 people.Data analysis techniques include Prerequisite Test and Simple Linear Regression Analysis and t Test. The results showed that Fhitung (0.3038) ˃ Ftabel (0.0725) which meant that the provision of rewards and student learning motivation with in a linear pattern, KP = 23.04% which meant that the reward for student learning motivation was of 23.04% and thitung (3,670) > ttabel (1,125).Based on the results of the study, it was concluded that there was a significant influence of rewarding to the the learning motivation of high-grade students of SD Inpres 3/77 Panyili. So, the better the reward given, the better the student's learning motivation